Teaching A Foreign Language Through Text! (Eurasian Scientific Herald, 2023)
This paper wants to study how we can use technology to teach foreign languages. We are looking at how technology is used in education, especially in foreign language classes. We want to understand the good and bad things about using technology in the classroom. The text is saying that visualisation is important in preventing exhaustion and fatigue in the foreign language classroom. This is because everyone is different and has different personality traits that need to be considered. The main focus of this research is on how presentations can help people learn a new language. Videoconferencing is being studied as a popular option due to its unique features and advantages